Improving Data Technology Warehouse Performance Using Filesystem with GZIP, LZJB and ZLE Compression - Suharjito Suharjito (Universitas Ciputra Surabaya, 2016)
Data warehouse application is commonly used by many corporations as an analytical platform to develop marketing strategy and give advantage edge to their business. Many times, data warehouse platform need to manage huge amount of data as it needs to extract, load and transform enterprise data from many sources. To improve performance of data warehouse system, compression has been used in various ways, both at database layer or at filesystem layer. Compression brings an other benefit as it reduce storage capacity therefore reduce cost. However compression also add data processing that may impact to overall application response time. In this research, three different compression algorithms which are zle, lzjb and gzip were tested on data warehouse filesystem to understand the performance impact and the capacity saving benefit. Using swingbench as the benchmark tool and oracle database 12c, it shows that zle is the best compression algoritm with performance improvement of 92%, follows by lzjb with 78% performance improvement and gzip with 53% improvement. In terms of compression ratio, gzip can deliver the highest with 3.31 compression ratio, follows by lzjb with 2.17 compression ratio and zle with 1.55 compression ratio. AW.